Panel on open library, scholarship and learning at Athabasca University - Anderson, Terry; Ives, Cindy; Elliott, Colin (Open Access Week 2010, 2010)
AUSpace: Building an effective institutional repository to support research communities and open access. AUSpace is Athabasca University’s (AU) digital content repository. Its goal is to preserve and disseminate AU scholarly materials and to promote open access. The presenter will discuss the organization of AUSpace, its benefits for Open Access support, researchers and organizations, and research findings of AUSpace use. Bibliography of the Athabasca River Basin: A digital tool for knowledge-building and open access. The Bibliography of the Athabasca River Basin (BARB) is being developed as an Open Access research tool to aid in the study and dissemination of research done within the basin. Open Access serves a dual role for this bibliography; it is an opportunity to ensure that the bibliography reaches the greatest number of researchers and helps to provide access to some of the immense research available on the basin. Our presentation will focus on how Open Access will benefit the BARB project.